2022
DOI: 10.1111/jpc.15950
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of functional abdominal pain disorders and functional constipation in adolescents

Abstract: Aim: Functional abdominal pain disorders (FAPDs) and functional constipation (FC) are the common functional gastrointestinal disorders in adolescents. We aimed to determine the prevalence of FAPDs and FC in adolescents using the Rome IV Questionnaire of Pediatric Gastrointestinal Symptoms and the factors associated with these two functional gastrointestinal disorders. Methods: A survey for the prevalence of FAPDs and FC in adolescents was carried out at two high schools. A translated and validated Thai version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 37 , 43 , 46 , 52 Meanwhile, the constipation rate diagnosed with the Rome IV was the lowest, at 4.4%, based on data analysed from five clinic-based studies, 50 , 56 , 57 , 58 , 62 and four community-based studies. 59 , 61 , 63 , 64 We revealed inconsistent results of constipation rates between Rome II and III. Although the only change from Rome II to Rome III was a shortened duration of symptoms (decreased from 3 to 2 months), 9 this discrepancy can be explained by Rome II being appropriate for the diagnosis of constipation in young children, 37 whereas Rome III were more suitable for school-age children and adolescents.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“… 37 , 43 , 46 , 52 Meanwhile, the constipation rate diagnosed with the Rome IV was the lowest, at 4.4%, based on data analysed from five clinic-based studies, 50 , 56 , 57 , 58 , 62 and four community-based studies. 59 , 61 , 63 , 64 We revealed inconsistent results of constipation rates between Rome II and III. Although the only change from Rome II to Rome III was a shortened duration of symptoms (decreased from 3 to 2 months), 9 this discrepancy can be explained by Rome II being appropriate for the diagnosis of constipation in young children, 37 whereas Rome III were more suitable for school-age children and adolescents.…”
Section: Discussionmentioning
confidence: 87%
“… 30 , 37 Of the 20 studies that used the Rome III, the constipation rate was much lower (12.3%, 95% CI 9.0–15.7%). Nine studies reported the constipation prevalence according to the Rome IV, 50 , 56 , 57 , 58 , 59 , 62 , 63 , 64 , 65 with a prevalence of 5.2% (95% CI 3.2–7.1%) ( Table 3 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations